Successful stimulation of myocardial ganglionic plexi by Tau-20 in the absence of cardiac damage - Li, Shengzhe; Kay, Jamie A.; Agha-Jaffar, Danya; Gao, Cindy S. Y.; Perkins, Justin; Koutsoftidis, Simos; Drakakis, Emm Mic; Cantwell, Chris D.; Wang, Liliang; Kanagaratnam, Prapa; Chowdhury, Rasheda A. (Frontiers in Physiology, 2025)
Atrial fibrillation (AF) is a major healthcare burden worldwide. The standard invasive treatment for AF that is resistant to pharmacological intervention is a pulmonary vein isolation (PVI) procedure. Ganglionated plexus (GP) ablation can be used as an adjunctive therapy to PVIs, which together reduce the likelihood of AF recurrence. High-frequency stimulation (HFS) is a technique used to identify ectopy-triggering GP sites. However, to locate GP sites, sequential HFS must be delivered over the whole atria. Therefore, ensuring the safety of HFS delivery is integral to avoid irreversible damage from excessive pacing. We tested the Tau-20 version 2 neural simulator, a prototype of a custom-built novel electrophysiological pacing and recording system (patent reference: ASW100372P.EPP) that has the potential to guide intracardiac AF treatments. Using an ex vivo porcine Langendorff model that closely resembles the anatomy and physiology of a human heart, we confirmed that HFS can successfully trigger AF, suggesting that HFS-positive locations contain GP sites. Additionally, we found that HFS delivered via Tau-20 version 2 did not cause any damage to the heart. These findings are evidence that once fully optimized, the Tau-20 system could be suitable for use in clinical settings.